Power and energy measurement devices: A review, comparison, discussion, and the future of research. (February 2021) - Babuta, Aniket; Gupta, Bhavna; Kumar, Abhimanyu; Ganguli, Souvik
Abstract: This paper presents a detailed survey on power and energy measurement devices capturing the overall progress over the decades in the associated field of instrumentation. The working principle of several devices along with their applications and advantages/disadvantages are provided in this review work. The implementation of wattmeter in a single-phase system along with three-phase system is also given. An appropriate apparatus is extremely important for proper evaluation of power transfer and energy consumption within a network. The development of energy measurement instruments from simple machines to complex computational structures with data transmission and processing ability is also discussed. A thorough description of smart meters and the internet of energy (IoE) follows thereafter. Finally, the future of the power sector in view of the present technology and the current situation of energy theft is also provided. This paper not only presents information but also indicates future direction for inquisitive researchers.